Analysis of the meaning of words in the book “Kumpulan Puisi Anak Sang Surya” as material for making teaching materials for new vocabulary mastery for grade IV elementary school students - Prakasa, Mahardika Teguh; Wardana, Deni; Maulana, Farid Rizqi (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Learning about vocabulary mastery is contained in the Independent Curriculum in Indonesian subjects, precisely in the learning achievements of phase B grades 3-4 elementary school on the elements of reading and watching, this is the basis for the importance of students in learning the mastery of new vocabulary and the meaning of these vocabulary. Poetry texts can be an alternative in learning to master students' new vocabulary, this is in line with the research entitled Penguasaan Kosakata terhadap Keterampilan Menulis Puisi Siswa delivered by Ramadhani (2020) From the results of his research, it is concluded that there is a significant interaction between the learning model and vocabulary mastery. The poetry texts used in the study are Kumpulan Puisi Anak Sang Surya written by Lia Maylani Hendriyanti. This research aims to find out the meaning of words in books Kumpulan Puisi Anak Sang Surya. In addition, this research also aims to obtain good teaching materials for the mastery of vocabulary of grade IV elementary school students based on the results of book analysis Kumpulan Puisi Anak Sang Surya. This research uses a qualitative approach with a method of analyzing the content of production flows and exchanging meanings called data. In this study, the words or morphemes contained in the collection of poems. Poems contained in the book Kumpulan Puisi Anak Sang Surya there are 34 poems, totaling 2,393 words. Words in the book Kumpulan Puisi Anak Sang Surya it has lexical and grammatical meanings, but is more likely to use grammatical meanings. By word denotative and the connotation that exists in poetry, not all poems are used as teaching materials for students' mastery of new vocabulary, there are 24 poems that will be used as teaching materials.
Keywords: analysis; meaning; poetry; teaching materials